ANALISIS KEPUASAN PELANGGAN DI KANTOR BPJS KESEHATAN KARANGANYAR - Intan Permata Sari; Hery Sawiji; Tri Murwaningsih (JIKAP (Jurnal Informasi dan Komunikasi Administrasi Perkantoran), 2019)
The objectives of the research are to determine: (1) the implementation of service system at the Office of Health Social Security Agency (BPJS) in Karanganyar; (2) the customer satisfaction at the Office of Health Social Security Agency (BPJS) in Karanganyar; (3) the obstacles faced in the application of service at the Office of Health Social Security Agency (BPJS) in Karanganyar; and (4) the solutions implemented to overcome obstacles that occur at the Office of Health Social Security Agency (BPJS) in Karanganyar. This research used qualitative approach methods with  case study type. The data source in this research derived from informant, place and event, as well as  document and archives. Data were collected by interview, observation, and document and archives analysis. The obtained data then were analyzed with interactive analysis technique consisted of data collection, data reduction, data presentation, and conclusion. Data validation was done by using source and method triangulations. The results showed that: (1) the service system used consisted of the direction by the officer, giving a queue number, and service; (2) customer satisfaction, which is related to the services offered according to the needs of participants, competent officers, and adequate facilities; (3) the obstacles that emerge in the service are the lack of participants' retention of the existence of MOBILE  JKN and insufficient space capacity during long queues; (4) efforts made in overcoming the obstacles are optimization of the JKN MOBILE function, addition of counters, additional waiting chairs, expansion of service space, and partnership.